Immobilization of environmental bacteria using microfluidic devices and industrial byproducts - Velásquez Yánez, Paola Mishell (2024)
Environmental bacteria play a crucial role in regulating ecosystem services and can be utilized in biotechnological products with innovative applications across various fields. Our studies focus on the immobilization of environmental bacteria for use in contaminant removal processes. Lab-on-a-chip technology applied to bacterial immobilization is an emerging area, offering the advantages of system miniaturization and low-cost analysis. The aim of this work was to evaluate the immobilization, through biofilm formation, of bacteria isolated from petroleum-contaminated environments using microfluidic devices (chips) as a support and a low-cost culture medium formulated with industrial byproducts. The planktonic growth of Pseudomonas sp. P26 (P26) and Rhodococcus sp. F27 (F27), bacteria selected for their ability to remove petroleum aromatic compounds, was assessed both in LB broth (a standard culture medium) and in the alternative medium based on corn steep water and crude glycerol. Planktonic growth was assessed by enumerating colony-forming units (CFU) per millilitre. In order to immobilize bacteria, polydimethylsiloxane (PDMS) chips with a glass base and an internal chamber volume of 300 µL were fabricated. The biofilm formation of P26 and F27 in the chips (at 30°C, for 72 hours with continuous flow) was evaluated in the low-cost culture medium. Biofilm formation was analyzed using electron microscopy and the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) technique to determine cellular metabolic activity. The growth of planktonic cultures and bacterial immobilization in the chips were successful for both P26 and F27, with P26 forming significantly more abundant biofilms than F27. Both strains developed complex, structured biofilms with intercellular connections and a moderate amount of extracellular material (in P26). These promising results in biomass immobilization on chips, using regional industrial byproducts, pave the way for the design of bioproducts with potential for environmental contaminant removal.